Development of Nipa palm fibers for textiles - Pimchutha Pigunthong; Nirat Soodsang (Caspian Journal of Environmental Sciences)
The purpose of this research was to study the physical properties of Nipa palm fibers and test the properties of the fibers obtained from the yarn-spinning process. In visiting community groups that produced Nipa palm products in many provinces in Thailand, it was found that the interesting part of Nipa palms that could be brought to develop, build a career, and add value to this plant was Nipa palm fibers, which are tough, strong, and suitable for making wicker products. Interestingly, Kan Mhong Jak (stalks of empty Nipa palm bunches) could be developed into fabrics for use in the design of various products. Additionally, the Nipa palm fibers were mixed with polyester fibers in two different proportions. They were then tested until getting suitable for weaving into the fabrics. The obtained woven fabrics were beautiful, strong, and suitable for further development and creation of other textile products. This can add value to the Nipa palm, a plan that occurs naturally in the community to maximize its benefits and become more well-known.